Water deities & mythical sea creatures - Zekrgoo, Amir Hossein (MATN Publishing, Iran Academy of Art, 2016)
This book is the 4th volume of a multi-volume series under the general title "Symbolism in Oriental Arts". Each volume is devoted to a certain symbol (animal, plant, human, gestures and postures, tools, etc.) within the religious traditions of the East. The present volume is compiled in 130 pages complemented with some 115 images (line drawings and color plates) and a glossary of technical terms.